Variation in Susceptibility to Wheat dwarf virus among Wild and Domesticated Wheat - Nygren, Jim; Shad, Nadeem; Kvarnheden, Anders; Westerbergh, Anna (PloS one, 2015)
We investigated the variation in plant response in host-pathogen interactions between wild (Aegilops spp., Triticum spp.) and domesticated wheat (Triticum spp.) and Wheat dwarf virus (WDV). The distribution of WDV and its wild host species overlaps in Western Asia in the Fertile Crescent, suggesting a coevolutionary relationship. Bread wheat originates from a natural hybridization between wild emmer wheat (carrying the A and B genomes) and the wild D genome donor Aegilops tauschii, followed by polyploidization and domestication. We studied whether the strong selection during these evolutionary processes, leading to genetic bottlenecks, may have resulted in a loss of resistance in domesticated wheat. In addition, we investigated whether putative fluctuations in intensity of selection imposed on the host-pathogen interactions have resulted in a variation in susceptibility to WDV. To test our hypotheses we evaluated eighteen wild and domesticated wheat taxa, directly or indirectly involved in wheat evolution, for traits associated with WDV disease such as leaf chlorosis, different growth traits and WDV content. The plants were exposed to viruliferous leafhoppers (Psammotettix alienus) in a greenhouse trial and evaluated at two time points. We found three different plant response patterns: i) continuous reduction in growth over time, ii) weak response at an early stage of plant development but a much stronger response at a later stage, and iii) remission of symptoms over time. Variation in susceptibility may be explained by differences in the intensity of natural selection, shaping the coevolutionary interaction between WDV and the wild relatives. However, genetic bottlenecks during wheat evolution have not had a strong impact on WDV resistance. Further, this study indicates that the variation in susceptibility may be associated with the genome type and that the ancestor Ae. tauschii may be useful as genetic resource for the improvement of WDV resistance in wheat.